P647 Is liver steatosis a risk factor for hepatotoxicity in patients with inflammatory bowel disease on thiopruines?. (16th January 2018) - Phillips, J; Preskey, R; Penfold, C; Tyrrell-Price, J; Gordon, F
Abstract: Background: The literature shows that inflammatory bowel disease (IBD) patients with hepatic steatosis do not tolerate the immunosuppression used in IBD. 1 We hypothesised that hepatic steatosis may be a risk factor for hepatoxicity in patients with IBD on azathioprine, and specifically whether MMP had a role in this process. Methods: To investigate this, we performed a retrospective review of patients started on azathioprine treatment at the Bristol Royal Infirmary between 2014 and 2017. There were 600 patients in total. One hundred and twenty-one patients met our inclusion criteria which were at least one ultrasound scan commenting on the appearance of the liver, liver function tests (LFTs) at commencement of azathioprine and liver function tests and an MMP level around 6 weeks after starting treatment. Results: Of 121 patients included in our study we identified 40 patients (33%) with radiological hepatic steatosis and 81 patients with no evidence of steatosis. We found (using a Wilcoxon rank-sum test) strong evidence to indicate that patients with hepatic steatosis had higher than expected MMP levels at 6 weeks ( p = 0.03). Our results also found that there is a positive association between MMP levels and change in ALT in patients with fatty liver ( p < 0.001). However, we found no association between either fatty liver status and ALT, or MMP and change in ALT alone. Conclusions: Our data suggest that patients with hepatic steatosis may metabolise azathioprine differently resulting in higher levels of MMP, consistent with previously published data. 2 We also conclude that the combination of liver steatosis and higher levels of MMP may be a risk factor for hepatitis. References: 1. Scroder T, Schmidt KJ, Oslen V et al. Liver steatosis is a risk factor for hepatoxicity in patients with inflammatory bowel disease under immunosuppressive treatment. Gastroenterol Hepatol, 2015;27:698–704. 2. Merrell MD, Cherrington NJ. Drug metabolism alterations in nonalcoholic fatty liver disease. Drug Metabolism Rev, 2011;43:317–34.